Optimization and Characterization of Biosurfactant Production from Marine Vibrio sp. strain 3B-2 - Hu, Xiaoke; Wang, Caixia; Wang, Peng (Frontiers in Microbiology, 2015)
A biosurfactant-producing bacterium, designated 3B-2, was isolated from marine sediment and identified as Vibrio sp. by 16S rRNA gene sequencing. The culture medium composition was optimized to increase the capability of 3B-2 for producing biosurfactant. The produced biosurfactant was characterized in terms of protein concentration, surface tension and oil-displacement efficiency. The optimal medium for biosurfactant production contained: 0.5% lactose, 1.1% yeast extract, 2% sodium chloride and 0.1% disodium hydrogen phosphate. Under optimal conditions (28°C), the surface tension of crude biosurfactant could be reduced to 41 from 71.5 mN/m (water), while its protein concentration was increased to up to 6.5 g/L and the oil displacement efficiency was improved dramatically at 6.5 cm. Two glycoprotein fractions with the molecular masses of 22 and 40 kDa were purified from the biosurfactant, which held great potential for applications in microbial enhanced oil recovery and bioremediation.